Ruthenium(II)-Catalyzed Selective C–H Bond Activation of Biindoles and Coupling with Sulfoxonium: An Efficient Access to Pyrido[1,2-a:4,3-b′]diindole frameworks - Jatoth, Ramanna; Gugulothu, Kishan; Valappil, Rasika Meloth; Nelson, Nithya; Kumar, K. Shiva (Synlett, 2023)
A ruthenium-catalyzed selective C–H functionalization/annulation cascade reaction of biindoles and sulfoxonium ylides has been developed. The reaction selectively provides pyrido[1,2-a:4,3-b′]diindole (5H-benzo[2,3]indolizino[7,8-b]indole) derivatives in good yields. A possible mechanism for the reaction pathway is proposed. More importantly, the present study provides a useful method for the construction of pyrido[1,2-a:4,3-b′]diindole frameworks.